PHYTOCHEMICAL PROFILE AND ANTIOXIDANT POTENTIAL OF ETHANOL EXTRACT FROM GATAL LEAVES (Laportea Decumana) OF MALUKU - Semuel Simra; Nikmans Hattu; Jolantje Latupeirissa (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Abstract This study aimed to evaluate the phytochemical profile and antioxidant activity of ethanol extract from Gatal leaves (Laportea decumana) sourced from Maluku. Dried leaf powder was extracted with 96% ethanol over three cycles of 24 hours, followed by concentration using a rotary evaporator. Qualitative phytochemical screening confirmed the presence of phenols, flavonoids, alkaloids, tannins, and terpenoids, while saponins and steroids were not detected. Phenols and flavonoids were identified as the dominant bioactive compounds responsible for strong antioxidant properties. Antioxidant activity was assessed using the DPPH assay, yielding an IC₅₀ value of 55.31 ppm slightly higher than the positive control, vitamin C (IC₅₀ = 47.20 ppm) indicating potent free radical scavenging ability. These findings confirm that the ethanol extract of Gatal leaves is rich in bioactive phytochemicals, particularly antioxidants, and holds significant potential as a natural raw material for the development of herbal or nutraceutical products.